Seismic vulnerability of reinforced concrete bridges in Pakistan - Hafiz, Muhammad Khalid; Khan, Qaiser-uz-Zaman; Ahmad, Sohaib (Journal of Civil Engineering and Management, 2022)
Different researchers have performed seismic hazard assessment studies for Pakistan using faults sources which differ from Building Code of Pakistan (BCP 2007) with diverse standard deviations. The results of seismic hazard studies indicate that BCP requires gross revision considering micro and macro level investigations. The recent earthquakes in Pakistan also damaged bridge structures and some studies have been conducted by different researchers to investigate capacity of existing bridges.The most of bridge stock in Pakistan has been designed assuming seismic loads as 2%, 4% and 6% of dead loads following West Pakistan Code of Practice for Highway Bridges. The capacity of eight selected real bridges, two from each seismic zone 2A, 2B, 3 & 4 is checked against BCP demands. Static and dynamic analyses were performed and the piers were checked for elastic limits. It is established that piers are on lower side in capacity and the bridges in zone 2A are generally less vulnerable. Whereas the bridges in zone 2B, 3 and 4 are vulnerable from medium to very high level. Hence, an in-depth analytical vulnerability study of bridge stock particularly in high-risk zone needs to be conducted on priority and appropriate seismic retrofitting schemes need to be proposed.